2013
DOI: 10.1128/jvi.02132-13
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Rabies Virus Phosphoprotein Gene in Neuroinvasiveness

Abstract: e Rabies virus (RABV), which is transmitted via a bite wound caused by a rabid animal, infects peripheral nerves and then spreads to the central nervous system (CNS) before causing severe neurological symptoms and death in the infected individual. Despite the importance of this ability of the virus to spread from a peripheral site to the CNS (neuroinvasiveness) in the pathogenesis of rabies, little is known about the mechanism underlying the neuroinvasiveness of RABV. In this study, to obtain insights into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 49 publications
4
60
0
1
Order By: Relevance
“…We previously reported that RABV P protein has a key role in both neuroinvasiveness and neurovirulence (21,22). This is supported by experimental data showing that chimeric mutant CE(NiP), which has the P gene from virulent Nishigahara (Ni) in the genome of the attenuated variant Ni-CE, caused lethal infection in mice after both intramuscular (i.m.)…”
supporting
confidence: 53%
See 3 more Smart Citations
“…We previously reported that RABV P protein has a key role in both neuroinvasiveness and neurovirulence (21,22). This is supported by experimental data showing that chimeric mutant CE(NiP), which has the P gene from virulent Nishigahara (Ni) in the genome of the attenuated variant Ni-CE, caused lethal infection in mice after both intramuscular (i.m.)…”
supporting
confidence: 53%
“…By using the same methods, we also obtained a recombinant CE(NiP)⌬P2-5 expressing firefly luciferase [CE(NiP)⌬P2-5-Luc] after inserting a PCR-amplified cDNA fragment of the luciferase gene into the G-L intergenic region of the above-described genome plasmid of CE(NiP)⌬P2-5 as previously reported (22,23). Details of the construction of the above-described genome plasmids will be provided by the authors on request.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…L protein functions were mostly predicted from studies on vesicular stomatitis virus. In recent years, reports about RABV were mainly focused on the viral G (5-7), P (8)(9)(10)(11)(12)(13)(14), M (15)(16)(17)(18), and N (9,(19)(20)(21)(22)(23)(24) proteins. However, the work on L protein of RABV has been relatively limited.…”
Section: Introductionmentioning
confidence: 99%